2018
DOI: 10.2147/ijn.s174072
|View full text |Cite
|
Sign up to set email alerts
|

Natural product-based nanomedicines for wound healing purposes: therapeutic targets and drug delivery systems

Abstract: Wound healing process is an intricate sequence of well-orchestrated biochemical and cellular phenomena to restore the integrity of the skin and subcutaneous tissue. Several plant extracts and their phytoconstituents are known as a promising alternative for wound healing agents due to the presence of diverse active components, ease of access, and their limited side effects. The development of nanotechnological methods can help to improve the efficacy of different therapeutics as well as herbal-based products. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
121
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(130 citation statements)
references
References 112 publications
1
121
0
8
Order By: Relevance
“…Nanobiotechnology is rapidly growing as an interdisciplinary eco‐friendly research area and used in broad research section such as biology, chemistry, physics, biomedicine and material engineering . It deals with various shapes and size of particles in the range of 1 to 100 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanobiotechnology is rapidly growing as an interdisciplinary eco‐friendly research area and used in broad research section such as biology, chemistry, physics, biomedicine and material engineering . It deals with various shapes and size of particles in the range of 1 to 100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Stapf, Drosera binata Labill., Eucalyptus globulus , Ficus religiosa , Fraxinus angustifolia , Indigofera aspalathoides DC., Lansium domesticum Corrêa, Melia dubia Cav., Momordica charantia L., Trigonella foenum‐graecum , Naringi crenulata (Roxb.) Nicolson, Nyctanthes arbor‐tristis L., Terminalia chebula Retz., Orchidantha chinensis T.L.Wu, Piper nigrum , and Phytophthora infestans …”
Section: Introductionunclassified
“…In recent years, use of chemicals has encouraged the researchers to conduct many studies on the use of traditional and herbal medicines. These studies have revealed that natural drugs are the only treatment modality in some cases, and the compounds available in them have been used in pharmaceutical industries . Because no definitive drug has been introduced for wound healing, it is necessary to perform studies on the effects of herbal drugs and their metal nanoparticles (NPs) on cutaneous wound healing .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed that natural drugs are the only treatment modality in some cases, and the compounds available in them have been used in pharmaceutical industries . Because no definitive drug has been introduced for wound healing, it is necessary to perform studies on the effects of herbal drugs and their metal nanoparticles (NPs) on cutaneous wound healing . A list of plants that are synthesized by metal NPs for increasing the cutaneous wound‐healing effects includes Piper nigrum , Phytophthora infestans , Terminalia chebula Retz., Orchidantha chinensis T.L.Wu, Naringi crenulata (Roxb.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation